MORPHOMETRIC STUDY OF Nerita lineata AND Littoraria melanostoma IN THE MANGROVE ECOSYSTEM OF INDUSTRIAL AND NON INDUSTRIAL AREAS IN SUNGAI SEMBILAN DISTRICT, DUMAI CITY, RIAU PROVINCE - Utami, Astri Hijri; Mulyadi, Aras; Amin, Bintal (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
Abstract N. lineata lives in tropical intertidal areas such as rocky shores, mud and also in mangrove trees while L. melanostoma lives in high ranges of areas in mangrove such as stems and leaves. This research was carried out on May 2018 in Sungai Sembilan District, Dumai City, Riau Province. This study aims to determine the morphometrics of N. lineata and L. melanostoma, the density of mangroves, and the relationships of density of mangroves with N. lineata and L. melanostoma populations in industrial and non-industrial areas. The sampling was done by using line transect method, carried out at 2 stations, station I in the industrial area and station II in the non-industrial area. The results showed that the highest length, width and weight of N. lineata and L. melanostoma were found in non-industrial areas. Simple linear regression analisis between length and wide of N. lineata and L. melanostoma are negative allometrics. The density of mangrove at industrial areas (1255.54 ind/ha) was higher than in non-industrial areas (1033.33 ind/ha). A weak relationship between mangrove density with N. Lineata density in the industrial area was observed (r=0.12), while in the non-industrial area has a moderate relationship (r=0.48). Meanwhile the density of mangroves with L. melanostoma density in industrial areas showed a very weak relationship (r=0.12) and conversely in non-industrial areas showed a strong relationship (r= 0.55).  Keywords: Morphometric, Nerita Lineata, Littoraria melanostoma, Mangrove